To Study the Association of Cyclin D1 Expression with Fuhrman’s Nuclear Grading in Renal Cell Carcinoma - M. Rizwan, Nazia Farooq, Hira Tariq, Ahmad Naeem Akhtar, Shazia. N Ibne-Rasa, Sumaira Naz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In adults, renal cell cancer (RCC) consists of tumors arising from the renal parenchyma and renal pelvis. Renal parenchyma cancer is mainly renal cancer i.e. adenocarcinoma. Renal pelvis malignancy is mainly transitional cell type. Presently, prognostic markers for renal cell cancer are tumor stage and nuclear grade. Aim: To observe the expression of cyclinD1 in different variants of RCC and to associate cyclinD1 expression with Fuhrman nuclear grades of RCC. Results: Out of 93 patients, 54(58.1%) were of more than 40 years of age, with M: F ratio of 1: 1. Clear cell RCC was the most common histological type i.e. 72out of 93(77.4%) biopsies. Low grades RCC were 50 out of 93(53.8%) and High grade RCC were in 43 out of 93(46.6%) biopsies and out of these 43 high grade RCC 23(24.7%) were found to invade surrounding tissue. As far as CyclinD1 expression score was concerned, 60 out of 93(64.4%) biopsies were found to have score 1 and 2 with no and upto30% +ve cells and 33(35.5%) biopsies were of score 3 and 4 with 30-60% and >60% positive cells respectively. In this study, 28 out of 93(30.2%) biopsies of low Fuhrman’s nuclear grade showed cyclin D1 score 3 and 4 respectively. Conclusion: In our study cyclin D1 protein was over expressed in low grade RCC showing that high protein levels may be related with the disease progression in patients of RCC. Cyclin D1 protein expression in future can be used as adjuvant to Fuhrman’s nuclear grading and will increase the predictive accuracy of the current disease progression models for RCC.